An Investigating of the Possibility of Religious Education Based on the Theory of Revelational Rationality, according to the Views of Allame Javadi Amoli - Parastou Mesbahi Jamshid (اخلاق وحیانی, 2019)
Most of the research have done in the field of education in the past twenty years has been in the tradition of analytical philosophy, and the most challenging one has been the denial of meaning and the possibility of religious education. Analytical philosophers of education, such as Hurst and Peters, emphasize free education and consider religious education as impossible, because it lacks the characteristics of being measurable, generalizable, and transferable. Their attitude to education is derived from an approach they have on the forms of knowledge; given this attitude, the knowledge is a matter whose principles are interdisciplinary and whose validity is abstracted from operation, not external. Their claim to reject religious education goes back to the indeterminate cognitive status of religion, the scientific nature of education, and the lack of rationality in religious education. In this study, the theory of revelational rationality, as a theoretical basis, is responsible for answering these problems. The findings of the study show that education and religion, because of their common theme and purpose, make a conceptual and meaningful combination. Religious education can also be established through the demonstration of religious science and the delineation of rationality. Religious rationality, by rejecting the implicit or persuasive view of the goal of education, introduces the revelational reason as the criterion of value and prosperity, neither the actions of rational people nor justified efficiency.  Also, the charge of lack of rationality in religious education that leads to a method of indoctrination, not education, is removed by addressing the religious meaning of indoctrination.  In this study, the human rational structure is identified with two aspects self-government and non-self-government, the first of which is associated with the will and the second with the validity of revelation.